2016
DOI: 10.1007/s10853-016-0148-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of freeze-drying conditions on aerogel properties

Abstract: Carbon nanofiber-reinforced polymer aerogels have been successfully synthesized by means of a freeze-drying process. The influence of the different operation conditions on both the process efficiency and the aerogel physical properties has been evaluated. Morphology, porosity and conductivity of the resulting carbon nanofiber-reinforced polymer aerogels were investigated. Their density and porosity increased when the freezing time decreased. However, the porosity of the carbon nanofiber-reinforced polymer aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…While the pressure drops, the temperature rises to eliminate any unfrozen or bound water deposits in the material [ 17 ]. In most circumstances, the ultimate goal of the final drying is to achieve a water content of 1 to 4% [ 208 ]. However, the sublimation rate during FD is generally observed to be prolonged.…”
Section: The Manufacture Of Aerogelsmentioning
confidence: 99%
“…While the pressure drops, the temperature rises to eliminate any unfrozen or bound water deposits in the material [ 17 ]. In most circumstances, the ultimate goal of the final drying is to achieve a water content of 1 to 4% [ 208 ]. However, the sublimation rate during FD is generally observed to be prolonged.…”
Section: The Manufacture Of Aerogelsmentioning
confidence: 99%
“…The size, structure and morphology of aerogel pores can be adjusted by changing the precursor material, its concentration or mixing it with other particles. The mechanical properties of aerogel have been reported to be affected by two main factors: precursor material and preparation method [ 48 ]. Yang et al [ 49 ] reported that cellulose enhanced the mechanical properties of the aerogel, and the ratio of alginate cellulose had a significant effect on the mechanical properties.…”
Section: Biopolymer-based Aerogelsmentioning
confidence: 99%
“…It can be observed in the obtained SEM figures that there are some differences in the morphology; CNCbased aerogel is spherical in shape while the CNFbased aerogel is rice-shaped, which results from the longer filament of CNF compared to CNC. The mechanical properties of aerogels have been reported to be affected by two main factors: precursor material and preparation method 46 . Cellulose is used to enhance the mechanical properties of many hybrid aerogels.…”
Section: Properties Of Cellulose-based Aerogelsmentioning
confidence: 99%